USAHA PENANGGULANGAN KEMISKINAN DI KABUPATEN PASURUAN PROPINSI JAWA TIMUR - Zulifah Chikmawati (UNEJ e-Proceeding)
Poverty is a complex phenomenon, multidimensional and can not be easily viewed from an only absolute numbers. Wide area and causing a big variety of cultural conditions and problems of poverty in the province of East Java become very diverse. The Research was taking a  deliberate location (purposive) in Pasuruan, because it was included in the typology of the coastal region, so the research was expected to determine the condition of poverty in coastal areas. The research used sampling methods FGD at regional government level, and followed by all agencies and FGDs at community level (community consultation), and FGD was held on the stage Rejo village and the village of Tuban district Sekargading Bugul South District. Constraints experienced by the Government of WordPress, was because prevention programs are implemented by local governments still can not be enjoyed by many or the majority of society, poverty reduction programs in Pasuruan still overlap. This was not optimal because of TKPKD role in implementing the synchronization and coordination of programs poverty reduction.